when subtracting a negative, change to positive and add.
google subtracting negatives.
I don't want the answer just instructions on how to do this please
Find the difference.
6 – (–9) = ?
4 answers
6 + 9 = 15
draw x axis
put your finger on 6
go left NEGATIVE 9 (opposite to positive 9) which means go right 9
draw x axis
put your finger on 6
go left NEGATIVE 9 (opposite to positive 9) which means go right 9
So take 6 - (-9) and make it
6 + (+9)
or 6 + 9
I recently studied this so I thought I would pitch in to help :)
6 + (+9)
or 6 + 9
I recently studied this so I thought I would pitch in to help :)
Or another way to do it.
When removing parentheses, if the sign before the parenthesis is + you leave the signs inside the parentheses as they are.
If the sign in front of the parenthesis is - you change all of the signs inside to the opposite. For example:
6 - (-9 + 15 + 6) = 6 + 9 - 15 - 6 = ?
6 + (-9 + 15 + 6) = 6 - 9 + 15 + 6 = ?
When removing parentheses, if the sign before the parenthesis is + you leave the signs inside the parentheses as they are.
If the sign in front of the parenthesis is - you change all of the signs inside to the opposite. For example:
6 - (-9 + 15 + 6) = 6 + 9 - 15 - 6 = ?
6 + (-9 + 15 + 6) = 6 - 9 + 15 + 6 = ?